Population Health: A New Paradigm for Medicine. (January 2016) - Peterson, Timothy A.; Bernstein, Steven J.; Spahlinger, David A.
ABSTRACT : N/A: Healthcare delivery system reform has become a dominant topic of conversation throughout the United States. Driven in part by ever‐higher national expenditures on health, an increasing number of payers and provider organizations are working to reduce the costs and improve the quality of healthcare. In this article, we demystify the term "Population Health, " review some of the larger payer initiatives currently in effect and discuss specific provider group efforts to improve the quality and cost of healthcare for patients.